Ochrona wizerunku w dobie tabloidyzacji mediów - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Examining modern media markets, one notices a common phenomenon of the predominance of tabloids, which are successful both in terms of readership and economic results. It is most likely the effectiveness and economic efficiency of what these media offer that results in a broader process of all media, whether printed or electronic, ‘contracting the tabloid virus’. This is the context within which media tabloidization is discussed, in the sense of the transformation of traditional, ‘noble’ media formats into social media, characterized by the prevalence of topics that arouse widespread interest (entertainment, celebrity scandals), shocking through sex and violence, and abounding in pictures, which is particularly significant from the point of view of this study. Additionally, press materials are shorter, which typically results in the simplified description of events, frequently violating the principles of good taste. The aim of this study is to suggest legal regulations on the matter of image protection in the context of media tabloidization.